2019
DOI: 10.1038/s41467-019-11624-9
|View full text |Cite|
|
Sign up to set email alerts
|

Copper-catalyzed dehydrogenative γ-C(sp3)-H amination of saturated ketones for synthesis of polysubstituted anilines

Abstract: Metal-catalyzed β -C-H functionalization of saturated carbonyls via dehydrogenative desaturation proved to be a powerful tool for simplifying synthesis of valuable β -substituted carbonyls. Here, we report a copper-catalyzed dehydrogenative γ -C(sp 3 )-H amination of saturated ketones that initiates the three-component coupling of saturated ketones, amines and N -substituted maleimides to construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…This result indicates that a Cu catalyst may not be responsible for 1,2‐aryl migration event, which is supported by the fact that a chiral pyridine oxazoline ligand gave no diastereoselectivity in the reaction of 2‐(3‐bromophenyl)‐1‐(4‐(tert‐butyl)phenyl)butan‐1‐one with chiral ( S )‐1‐cylohexylethan‐1‐amine, similar to the reaction outcome with nonchiral bipyridine ligand. Our previous work confirmed that γ‐keto enal resulted from oxygenation of γ‐C−H of enone [10] . These experiments shed light on the possible intermediate products in the cascade reaction of α‐aryl‐substituted alkyl aryl ketone with primary amine.…”
Section: Methodssupporting
confidence: 81%
See 3 more Smart Citations
“…This result indicates that a Cu catalyst may not be responsible for 1,2‐aryl migration event, which is supported by the fact that a chiral pyridine oxazoline ligand gave no diastereoselectivity in the reaction of 2‐(3‐bromophenyl)‐1‐(4‐(tert‐butyl)phenyl)butan‐1‐one with chiral ( S )‐1‐cylohexylethan‐1‐amine, similar to the reaction outcome with nonchiral bipyridine ligand. Our previous work confirmed that γ‐keto enal resulted from oxygenation of γ‐C−H of enone [10] . These experiments shed light on the possible intermediate products in the cascade reaction of α‐aryl‐substituted alkyl aryl ketone with primary amine.…”
Section: Methodssupporting
confidence: 81%
“…In light of such a potential reaction diversity, these dehydrogenative desaturation‐triggered cascade reactions promisingly complement the regular metal‐catalyzed direct C(sp 3 )‐H functionalization reactions [9] by generating the formal C−H functionalization products that are not easy to access by way of other approaches. To date, the vast majority of the established dehydrogenative desaturation‐triggered cascade reactions of carbonyl compounds have focused on the β‐functionalization reactions, and the examples of the dehydrogenative desaturation‐triggered cascade towards the remote C−H functionalization of carbonyl compounds have been extremely scarce [7c, 10] . Our recent investigations on the metal‐catalyzed dehydrogenative desaturation‐triggered cascade reactions of ketones have uncovered that α,β‐desaturation of ketone leads to the activation of γ‐Csp 3 −H bond [11] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism involves Chan-Lam arylation between arylboronic acid 302 and ester (Z)-3-aminoacrylates 123 under Hu et al established the dehydrogenative coupling of saturated ketones through γÀ C(sp 3 )À H amination using copper as the catalyst for the synthesis of polysubstituted anilines (343). [75] Amines (341), saturated ketones (340), and N-substituted maleimides (342) were reacted in the presence of 10 mol% Cu(OAc) 2 and 10 mol% 2, 2'-bipyridine(bpy) as a catalyst, 3 equiv. 2, 2, 6, 6-tetramethylpiperidine-N-oxide (TEMPO) as oxidant, p-TsOH as additive, and PhCH 3 as solvent at 120°C for 48 h under N 2 atmosphere (Scheme 103).…”
Section: Cà Si Bond Formationmentioning
confidence: 99%